COMPETITIVE ADVANTAGE AND EDUCATIONAL BRANDING IN ISLAMIC EDUCATION:: A Bibliometric Exploration - Girsang, Tetty Efriyanti; Saud, Udin S.; Permana, Johar; Abubakar, Abubakar; Ali Raza, Hafiz (Conciencia, 2025)
This study aims to map research trends and patterns on competitive advantage and educational branding within higher education institutions, particularly those related to Islamic education, from 2020 to 2025. Using a bibliometric research design, data were collected from the Scopus database with inclusion criteria covering journal articles published in the fields of educational management, Islamic education, and institutional development. A total of documents (to be filled based on actual data) were analyzed through VOSviewer and Bibliometrix to generate visual and quantitative insights regarding co-authorship networks, keyword co-occurrence, citation structures, and emerging thematic clusters. The findings reveal four dominant research themes: strategic branding and institutional competitiveness, globalization impacts on higher education including Islamic institutions, internal branding and human capital development in educational settings, and digital engagement through social media platforms to strengthen institutional reputation. These results highlight the increasing significance of digital branding and social marketing strategies in positioning Islamic educational institutions within a competitive global environment. The study concludes that strengthening competitive advantage requires an integration of external communication strategies and internal organizational capacity, aligned with contemporary branding theories such as brand equity, Resource-Based View (RBV), and Integrated Marketing Communication (IMC). This bibliometric analysis contributes to understanding how Islamic higher education institutions respond to global competition challenges and offers directions for future research and practical policymaking in educational branding.